Determining User Comfort With Bank Syariah Indonesia: Perspectives On Electronic Word Of Mouth And Brand Image - Nuri Aslami; Ali Ikhwan (Yayasan Darussalam Bengkulu, 2026)
Background: Indonesia’s Islamic banking sector continues to expand, with Bank Syariah Indonesia (BSI) playing a major role in asset growth and digital service adoption. Despite increasing use of BSI Mobile, customer complaints about digital service reliability have generated negative electronic word-of-mouth (e-WOM) that may affect brand image and user trust. Most previous studies focus on purchase intention and loyalty, while limited research examines user comfort. Therefore, this study analyzes the influence of e-WOM and brand image on user comfort in using BSI Mobile services. Method: This study employed a quantitative approach to examine the influence of Electronic Word of Mouth and Brand Image on User Comfort. The population consisted of 991 Sharia Banking students at UIN North Sumatra who use BSI Mobile. Using the Slovin formula, a sample of 91 respondents was selected based on specific usage criteria. Data were collected through questionnaires distributed via Google Forms, supported by observation and documentation, and analyzed using Multiple Linear Regression. Results: The findings show that user comfort is positively and significantly impacted by e-WOM and brand image, both partially and concurrently. e-WOM and brand image account for 62.3% of the variation in user comfort, according to the coefficient of determination (R²) of 0.623. These results imply that improving user satisfaction in Islamic digital banking services requires positive digital evaluations and a strong brand image. Conclusion: The results show that Electronic Word of Mouth (e-WOM) and Brand Image have a significant and positive effect on user comfort in using BSI Mobile services, both partially and simultaneously, with a coefficient of determination (R²) of 0.734. These findings indicate that strengthening positive digital communication and maintaining a strong brand image are essential strategies to enhance user comfort and trust in digital Islamic banking services.